Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fimmu.2018.02178
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Lactobacillus delbrueckii TUA4408L and Evaluation of the Antiviral Activities of its Extracellular Polysaccharides in Porcine Intestinal Epithelial Cells

Abstract: In lactic acid bacteria, the synthesis of exopolysaccharides (EPS) has been associated with some favorable technological properties as well as health-promoting benefits. Research works have shown the potential of EPS produced by lactobacilli to differentially modulate immune responses. However, most studies were performed in immune cells and few works have concentrated in the immunomodulatory activities of EPS in non-immune cells such as intestinal epithelial cells. In addition, the cellular and molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 48 publications
7
44
0
Order By: Relevance
“…In this regard, we have evaluated whether LAB strains induce the expression of IFN-β in HCT116 cells. We found that LABs stimulation increased the expression of IFN-β in response to PolyI:C. Our findings are in good agreement with the results of others studies obtained for Bifidobacterium infantis MCC12 and B. breve MCC1274 (3), Lactobacillus casei MEP221106 (16), Lactobacillus delbrueckii TUA4408L (29), and L. casei Zhang (34). Probiotic L. acidophilus NCFM was able to increase the expression of IFN-β in bone marrow derived dendritic cells in vitro (35).…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, we have evaluated whether LAB strains induce the expression of IFN-β in HCT116 cells. We found that LABs stimulation increased the expression of IFN-β in response to PolyI:C. Our findings are in good agreement with the results of others studies obtained for Bifidobacterium infantis MCC12 and B. breve MCC1274 (3), Lactobacillus casei MEP221106 (16), Lactobacillus delbrueckii TUA4408L (29), and L. casei Zhang (34). Probiotic L. acidophilus NCFM was able to increase the expression of IFN-β in bone marrow derived dendritic cells in vitro (35).…”
Section: Discussionsupporting
confidence: 92%
“…Research from the last decade investigating the immunobiotic effector molecules has demonstrated that each individual immunobiotic strain has a characteristic set of molecules, which are responsible of its interaction with the host's immune receptors (28)(29)(30). Surface molecules of immunobiotic microorganisms, including exopolysaccharides, cell wall peptidoglycan, and LTA, have been frequently associated with their immunomodulatory effects (28,29,31,32). In this regard, several reports have emphasized the importance of LTA in the immunomodulatory properties of some probiotic lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of EPSs derived from LAB to differentially modulate the innate antiviral immune response in IECs was not addressed in details before. In this regard, we have previously investigated the capacity of EPSs produced by the immunobiotic strains Lactobacillus delbrueckii OLL1073R-1 (Kanmani et al, 2018a) and Lactobacillus delbrueckii TUA4408L (Kanmani et al, 2018b) to beneficially modulate the innate immune response in PIE cells. This in vitro system has been particularly useful for the FIGURE 5 | Effect of cell-free supernatants (CS) from Streptococcus thermophilus ST538 and its exopolysaccharide (eps) mutant strains on the innate antiviral immune response triggered by Toll-like receptor 3 (TLR3) activation in porcine intestinal epithelial cells (PIE cells).…”
Section: Discussionmentioning
confidence: 99%